The social sustainability of cities : diversity and the management of change - Polèse, Mario, 1943-; Stren, Richard E. (University of Toronto Press, 2000)
Some cities have been more successful than others in creating environments conducive to the cohabitation of a diverse population. Case studies analyze ten cities in North America, South America, Europe, and Africa in terms of their social sustainability.